2003
DOI: 10.1590/s1517-83822003000500038
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of poly (epsilon-caprolactone) and poly (vinyl chloride) blend

Abstract: Poly(caprolactone) is a famous biodegradable polymer and miscible with PVC, a commercial synthetic polymer, thermal susceptible and non-biodegradable. This blend is important concerning its mechanical properties and biodegradability. In this work, we testified the biomodification of blend films of PVC/PCL by UV-Vis. spectroscopy. The results show us that there is an interaction between the PVC/PCL film and the microrganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In another study about 3% reduction in the molar mass of pPVC (DOP) was observed after 3‐month soil burial experiment . The microorganism adherence brings some structural changes in PCL and PVC plastics having more carbonyl groups observed by UV–Vis spectrometer . The fungal isolates were found to be principal colonizer on the plasticized PVC film.…”
Section: Introductionmentioning
confidence: 92%
“…In another study about 3% reduction in the molar mass of pPVC (DOP) was observed after 3‐month soil burial experiment . The microorganism adherence brings some structural changes in PCL and PVC plastics having more carbonyl groups observed by UV–Vis spectrometer . The fungal isolates were found to be principal colonizer on the plasticized PVC film.…”
Section: Introductionmentioning
confidence: 92%
“…The films of PVC, PCL, PET and PVC/PCL blend were obtained by the evaporation of solutions diluted in dichloroethane (Tedia) at 60°C, with manual agitation during approximately 1 h. After this procedure, they were put in Petri dishes, dried at room temperature for 2 days and for more 2 days under vacuum [13].…”
Section: Polymeric Films and Glass Surfacesmentioning
confidence: 99%
“…It can be utilized by micro-organism as a reserved material at the time of its need (13). As it has material properties (Molecular weight, Melting temperature, Glass transition temperature) similar to synthetic polymers (24), it is trusted to triumph over the problems and harmful effects of plastic wastes (3,16,22).…”
Section: Introductionmentioning
confidence: 99%